2022
DOI: 10.3390/ijerph19137890
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Artificial Intelligence in Education on Adolescents’ Social Adaptability: A Machine Learning Study

Abstract: This study aimed to investigate the influence of artificial intelligence in education (AIEd) on adolescents’ social adaptability, as well as to identify the relevant psychosocial factors that can predict adolescents’ social adaptability. A total of 1328 participants (meanage = 13.89, SD = 2.22) completed the survey. A machine-learning algorithm was used to find out whether AIEd may influence adolescents’ social adaptability as well as the relevant psychosocial variables, such as teacher–student relations, peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The results of the study confirm the adaptability of educational AI solutions identified in the publication (Xie et al, 2022): intelligent AI systems can customise content and tasks according to learning progress, contributing to a more efficient learning process.…”
Section: Discussionsupporting
confidence: 72%
“…The results of the study confirm the adaptability of educational AI solutions identified in the publication (Xie et al, 2022): intelligent AI systems can customise content and tasks according to learning progress, contributing to a more efficient learning process.…”
Section: Discussionsupporting
confidence: 72%
“…These factors play a crucial role in effective learning and motivation. Incorporating social interactions, emotional support, and feedback mechanisms into AIED design can enhance the overall learning experience (Xie et al, 2022). For instance, Lai et al (2023) noted the need for the development of social adaptability in AIED system.…”
Section: Current Problems In Aied Designsmentioning
confidence: 99%
“…So that artificial intelligence can be embedded in the learning media created. The existence of artificial intelligence will add value to the usefulness of the media [42,43]. R12B states: The development of science and technology today, allows students to access various learning media available in cyberspace.…”
Section: Question 2: What Media Do Lecturers Use In Teaching Topics I...mentioning
confidence: 99%